2002
DOI: 10.1001/archsurg.137.6.696
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Safety of Enoxaparin Prophylaxis for Venous Thromboembolism in Patients With Intracranial Hemorrhagic Injuries

Abstract: Background: Patients with traumatic intracranial hemorrhagic injuries (IHIs) are at high risk for venous thromboembolism (VTE). The safety of early anticoagulation for IHI has not been established.Hypothesis: Enoxaparin can be safely administered to most patients with IHI for VTE prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 21 publications
1
89
1
2
Order By: Relevance
“…18 Alternatively, enoxaparin has also been used in a selective postoperative neurosurgical patient population within 48 hours after surgery, decreasing incidence of DVTs from 4.8% to 0% with no associated increase in ICH. 2,9,11,16,20 Other studies have shown some efficacy of chemoprophylaxis in selected trauma patients with head injury. 1,14,15,21,22 Based on these studies, our trauma center adopted a new clinical protocol to initiate VTE chemoprophylaxis 24 hours following injury after demonstration of stable ICH verified by CT scan.…”
mentioning
confidence: 99%
“…18 Alternatively, enoxaparin has also been used in a selective postoperative neurosurgical patient population within 48 hours after surgery, decreasing incidence of DVTs from 4.8% to 0% with no associated increase in ICH. 2,9,11,16,20 Other studies have shown some efficacy of chemoprophylaxis in selected trauma patients with head injury. 1,14,15,21,22 Based on these studies, our trauma center adopted a new clinical protocol to initiate VTE chemoprophylaxis 24 hours following injury after demonstration of stable ICH verified by CT scan.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] An exception to this general rule was the work of Berne and Norwood, who had promulgated a set of intracranial injury patterns that could safely receive enoxaparin 30 mg subcutaneously beginning 24 h after injury if a repeat CT scan of the head was stable. [6][7][8] Using their work as a starting point, our group modified these criteria and created the Parkland Protocol. This original version of the protocol …”
Section: Discussionmentioning
confidence: 99%
“…These investigations also suggested that this prophylaxis protocol should be administered after 24 hour from all initial and subsequent craniotomies. However, it is well known that preoperative usage of anticoagulants could increase the risk of the intra-cerebral hemorrhage related to the surgery 5,16) . Our patient's frontal skin edema and periorbital edema made us to suspect from the dural venous sinus thrombosis especially cavernous sinus thrombosis; and to avoid from severe complications of this (such as hemiparesis, blindness, debility, etc.)…”
Section: Discussionmentioning
confidence: 99%